The importance of socio-demographic indicators in regional disparities in turkey, 1990-1994 - Ayse Gedik; Nihan Sahin; Sibel Suer (European Regional Science Association (ERSA), 2002)
The aim of this study is to test the relative importance of the socio-demographic versus economic variables in discriminating the inter-regional differences in Turkey in 1990-94. Our findings show that the "socio-demographic" variables are much more significant than the "economic" variables. Among the socio-demographic variables, especially those variables related with the fertility and the size of household, and the female education such as the "female literacy ratio" and "female schooling ratio in high school", are the most effective variables rather than the economic variables, in the explanation of the differences between the regions in Turkey. Moreover, among the economic variables, the variables such as the "ratio of non-agricultural active population" are the more significant than the "GDP per capita" which is widely used as an ultimate indicator of socio-economic development. In this study, discriminant and factor analyses, and logistic regression are applied in total of five different methods. The tests are carried out for the seven regions of Turkey as defined by the State Institute of Statistics. Subsequently the analyses are repeated by combining these seven regions into three regions and two regions. Our above stated findings were always consistent in each of these tests. Our data sources are the various publications of State Institute of Statistics (SIS) and State Planning Organization (SPO). The regional data are the unweighted arithmetic mean of the respective provinces. Key words: Regional disparity, Socio-demographic variables, Economic variables, Discriminant anlysis, Logistic regression, and Factor analysis.
Keywords: 330